Comparative analysis between RQ‐PCR and digital droplet PCR of BCL2/IGH gene rearrangement in the peripheral blood and bone marrow of early stage follicular lymphoma. (17th April 2017) - Cavalli, Marzia; De Novi, Lucia Anna; Della Starza, Irene; Cappelli, Luca Vincenzo; Nunes, Vittorio; Pulsoni, Alessandro; Del Giudice, Ilaria; Guarini, Anna; Foà, Robin
Summary: BCL2/IGH rearrangements were analysed by polymerase chain reaction (PCR) at diagnosis in paired peripheral blood (PB) and bone marrow (BM) samples from 67 patients with stage I/II follicular lymphoma (FL). Real time quantitative PCR (RQ‐PCR) and digital droplet PCR (ddPCR) were performed in cases with a major breakpoint region (MBR+) at diagnosis and after localized radiotherapy and rituximab administration in order to investigate the applicability of ddPCR. The overall ddPCR/RQ‐PCR concordance was 81·9% (113/138 samples) and 97·5% in the 40/138 with quantifiable disease (RQ‐PCR≥10 −5 ). At baseline, ddPCR allowed the recovery of a MBR+ marker in 8/18 (44·4%) samples that resulted MBR‐negative/minor cluster region‐negative/minor BCL2 ‐negative by qualitative PCR. Moreover, the tumour burden at diagnosis significantly predicted progression‐free survival (PSF) only when quantified by ddPCR. Paired PB and BM samples analysis demonstrated a high concordance in the detection of BCL2/IGH+ cells by qualitative and quantitative methods; in particular, 40/62 samples were positive by ddPCR (25 PB+/BM+; 9 PB+/BM−; 6 PB−/BM+), with 34/40 (85%) identified by the study of PB only. In conclusion, in localized FL, ddPCR is a promising tool for monitoring minimal residual disease (MRD) that is at least comparable to RQ‐PCR and potentially more accurate. PB is a suitable source for serial BCL2/IGH MRD assessments, regardless of the methodology utilized.